2021
DOI: 10.3389/fonc.2021.605847
|View full text |Cite
|
Sign up to set email alerts
|

Combination IETA Ultrasonographic Characteristics Simple Scoring Method With Tumor Biomarkers Effectively Improves the Differentiation Ability of Benign and Malignant Lesions in Endometrium and Uterine Cavity

Abstract: ObjectivesTo evaluate International Endometrial Tumor Analysis (IETA) ultrasonographic characteristics simple scoring method and tumor biomarkers for the diagnosis of uterine cavity and endometrial lesions.MethodsWe classified and scored the normalized description of IETA ultrasonic characteristics, according to IETA expert consensus literature, previous IETA-related research articles, and the previous research experience of this project group. We conducted a retrospective analysis of the ultrasound images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Tumor markers, notably CA125, CA199, and HE4, play a pivotal role in EC's pathological trajectory. 19 Notably, CA125, an endometrial-secreted glycoprotein antigen, stands out as a primary EC diagnostic tool. Investigations by Kakimoto S et al 20 revealed markedly elevated serum CA125 levels in EC patients compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers, notably CA125, CA199, and HE4, play a pivotal role in EC's pathological trajectory. 19 Notably, CA125, an endometrial-secreted glycoprotein antigen, stands out as a primary EC diagnostic tool. Investigations by Kakimoto S et al 20 revealed markedly elevated serum CA125 levels in EC patients compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…The submucous myomas protruded from the myometrium to the uterine cavity, often resulting in interrupted echo at the endometrial–myometrial junction; it would be overestimated by ultrasound GI-RADS scoring system, resulting in false positives. We could distinguish these lesions from EC by combining the “circular vessels” vascular pattern (in this study, the pathological results of all cases with the circular vessels vascular pattern were submucosal myomas), the characteristics of hypoechoic lesions and pseudocapsule sign (EC were often hyperechoic or mixed echoic, and their boundaries were often unclear) [ 29 ]. However, in this study, we also found that EC lesions of the non-endometrioid adenocarcinoma type may also be hypoechoic, quasi-circular in shape, and had scarce blood flow, which may be misdiagnosed as submucous myomas.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we normalized the description of IETA ultrasonic features and classified them into GI-RADS classification system according to the IETA expert consensus literatures [ 9 , 10 , 18 ], the IOTA simple standard method, the criteria used for GI-RADS adnexal tumors classification [ 43 ], the previous research experience of our project team [ 29 ] and the correlation between ultrasound features defined by IETA and benign and malignant lesions. The objective was to use standard descriptions to help sonographers classify intrauterine and endometrial lesions to distinguish between benign and malignant lesions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modalities may be ultrasound, saline infusion sonography, computerized tomography scanner, magnetic resonance imaging, hysteroscopy, endometrial biopsy, etc. [ 14 15 16 17 18 ] However, some modalities remain expensive for assessment in low- and middle-income countries such as Vietnam. Meanwhile, the physician can firstly approach to initial features, evaluate carefully clinical symptoms, and classify the degree of anemia prior to investigate by additional diagnostic modalities as ultrasound, biopsy, and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%